Description of a Novel Phosphodiesterase (PDE)-3 Inhibitor Protecting Mice From Ischemic Stroke Independent From Platelet Function. Issue 2 (February 2019) - Bieber, Michael; Schuhmann, Michael K.; Volz, Julia; Kumar, Gangasani Jagadeesh; Vaidya, Jayathirtha Rao; Nieswandt, Bernhard; Pham, Mirko; Stoll, Guido; Kleinschnitz, Christoph; Kraft, Peter
Abstract : Background and Purpose—: Acetylsalicylic acid and clopidogrel are the 2 main antithrombotic drugs for secondary prevention in patients with ischemic stroke (IS) without indication for anticoagulation. Because of their limited efficacy and potential side effects, novel antiplatelet agents are urgently needed. Cilostazol, a specific phosphodiesterase (PDE)-3 inhibitor, protected from IS in clinical studies comprising mainly Asian populations. Nevertheless, the detailed mechanistic role of PDE-3 inhibitors in IS pathophysiology is hardly understood. In this project, we analyzed the efficacy and pathophysiologic mechanisms of a novel and only recently described PDE-3 inhibitor (substance V) in a mouse model of focal cerebral ischemia. Methods—: Focal cerebral ischemia was induced by transient middle cerebral artery occlusion in 6- to 8-week-old male C57Bl/6 wild-type mice receiving substance V or vehicle 1 hour after ischemia induction. Infarct volumes and functional outcomes were assessed between day 1 and day 7, and findings were validated by magnetic resonance imaging. Blood-brain barrier damage, as well as the extent of local inflammatory response and cell death, was determined. Results—: Inhibition of PDE-3 by pharmacological blockade with substance V significantly reduced infarct volumes and improved neurological outcome on day 1 and 7 after experimental cerebral ischemia. Reduced blood-brain barrier damage, attenuated brain tissue inflammation, and decreased local cell death could be identified as potential mechanisms. PDE-3 inhibitor treatment did neither increase the number of intracerebral hemorrhages nor affect platelet function. Conclusions—: The novel PDE-3 inhibitor substance V protected mice from IS independent from platelet function. Pharmaceutical inactivation of PDE-3 might become a promising therapeutic approach to combat IS via inhibition of thromboinflammatory mechanisms and stabilization of the blood-brain barrier. Abstract : Supplemental Digital Content is available in the text.